Photoinduced anti-swelling biological adhesive as well as preparation method and application thereof
Through light-induced anti-swelling bioadhesive, the hydrogel network structure is formed by using biomacromolecules and porous silica of grafted temperature-sensitive polymers. Combined with the modification of bioactive peptides, existing bioadhesive agents are solved. Poor swelling and toxicity problems have achieved efficient tissue adhesion and healing effects.
Patent Information
- Application Number
- CN202411369573.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-31
AI Technical Summary
Existing bioadhesives are prone to swell after tissue damage, resulting in weakening of adhesion and re-rupture of wounds. There are toxic components and uncontrollable biodegradation problems, which cannot meet clinical needs.
Using light-induced anti-swelling biobinder, a hydrogel network structure is formed through biomacromolecules and porous silica of grafted temperature-sensitive polymers, and biological growth factors are loaded in the silica pores to bind to biological activity. The modification of the peptide forms a tight network structure to improve antiswelling and hemostatic properties.
Effective adhesion and repair of biological tissues is achieved, anti-swelling performance is improved, compression of soft tissue is avoided, wound healing is promoted, and the healing and coagulation of damaged tissues is accelerated by loading biological growth factors.
Smart Images

Figure CN119215220A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomedical adhesives, and in particular to a light-induced anti-swelling bioadhesive and a preparation method and application thereof. Background Art
[0002] After tissue damage, massive bleeding and wound infection are the main causes of death. Although sutures and staples are the most common methods for wound closure in clinical treatment, their operation is time-consuming and technically demanding, making them unsuitable for many emergency situations, such as sudden natural disasters and wars. In addition, sutures and staples often cause secondary tissue damage and leakage of fluids or gases, especially in fragile internal organs.
[0003] Tissue adhesives have been used for wound closure, hemostasis, prevention of anastomotic leakage, and accelerated wound healing. However, commercially available adhesives still cannot meet clinical requirements due to their weak tissue adhesion, toxic components, and uncontrolled biodegradation.
[0004] For tissue adhesives, ensuring ideal bonding mechanisms, biocompatibility, and biodegradability remains a major challenge for their practical application and clinical transformation (Ren et al., Sci. Adv., 2023, 9, 4327). Existing bioadhesives have high swelling behavior after absorbing blood and interstitial fluid (Guo et al., Sci. Adv., 2021, 7, 9635). The resulting weakening of cohesion and impaired adhesion may lead to undesirable performance and unpredictable results, or even re-rupture and re-bleeding of the wound (Bian et al., Adv. Funct. Mater., 2022, 32, 2207741). It is easy to form compression damage to soft tissues such as blood vessels and brain tissue. Once damaged, the symptoms will gradually worsen, resulting in impaired motor function or even paraplegia in patients (Lima et al., Int. J. Mol. Sci., 2020, 21, 5062). Therefore, developing bioadhesives with anti-swelling properties and excellent adhesion and hemostatic properties is more in line with clinical needs. Summary of the invention
[0005] In view of the above defects or improvement needs of the prior art, the present invention provides a preparation and application of a light-induced anti-swelling bioadhesive, the purpose of which is to effectively replace traditional surgical sutures for biological tissue adhesion and repair, achieve vascular occlusion and hemostasis, wound adhesion and good anti-swelling performance.
[0006] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a light-induced anti-swelling bioadhesive is provided, comprising biomacromolecules, bioactive peptides and porous silica grafted with thermosensitive polymers, wherein the biomacromolecules and the porous silica grafted with the thermosensitive polymers form a hydrogel network structure through a cross-linking reaction, and the bioactive peptides are connected to the biomacromolecules through a free radical cross-linking reaction.
[0007] Preferably, the chain ends of the biomacromolecule contain double bonds.
[0008] Preferably, the biomacromolecule is one or more of methacrylamide gelatin, methacrylamide silk fibroin, methacrylamide hyaluronic acid, methacrylamide chondroitin sulfate, methacrylamide sodium alginate, methacrylamide chitosan, methacrylamide dextran, methacrylamide heparin, polyether diacrylate, polyethylene glycol diacrylate, four-arm polyethylene glycol acrylate, and methacrylamide polyvinyl alcohol.
[0009] Preferably, the porous silica grafted with the thermosensitive polymer is formed by connecting the carboxyl groups in the thermosensitive polymer with the amino groups in the amino-modified silica through reaction grafting.
[0010] Preferably, the temperature-sensitive polymer is poly (N-isopropylacrylamide) modified with thiol and carboxyl groups.
[0011] Preferably, biological growth factors are loaded into the pores of the porous silica grafted with the thermosensitive polymer.
[0012] Preferably, the biological growth factor is one or more of epidermal growth factor, fibroblast growth factor, nerve growth factor, platelet-derived growth factor, and transforming growth factor.
[0013] Preferably, the bioactive peptide is prepared by modifying the side chain of the biopeptide with catechol, and the terminal group of the biopeptide is modified with methacrylic acid or acrylic acid.
[0014] According to another aspect of the present invention, there is provided a method for preparing the light-induced anti-swelling bioadhesive, comprising the following steps:
[0015] (1) dissolving biomacromolecules, bioactive peptides, porous silica grafted with thermosensitive polymers, and initiators in physiological saline, uniformly mixing, and degassing to obtain a prepolymer solution;
[0016] (2) The prepolymer solution is then irradiated with ultraviolet light or blue light to initiate photocuring of the prepolymer solution to form a bioadhesive.
[0017] Preferably, the amount of biomacromolecules in the prepolymer solution is 5wt%-20wt%, the amount of bioactive peptides in the prepolymer solution is 1wt%-5wt%, the amount of drug-loaded porous silica grafted with thermosensitive polymers in the prepolymer solution is 5wt%-20wt%, and the content of initiator in the prepolymer solution is 0.1wt%-5wt%.
[0018] Preferably, the initiator is selected from one or more of 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, phenyl-2,4,6-trimethylbenzoyl lithium phosphite, and Eosin Y. When the prepolymer liquid used is Eosin Y, a co-initiator is required.
[0019] Preferably, the co-initiator is selected from one or both of triethanolamine and pentamethyldiethylenetriamine.
[0020] According to another aspect of the present invention, there is provided a use of the light-induced anti-swelling bioadhesive in preparing a bioadhesive for promoting adhesion and repair of biological tissues or for occluding and stopping bleeding of blood vessels.
[0021] The reaction principle of the present invention is as follows: the drug-loaded porous silica grafted with a thermosensitive polymer is grafted and connected by reacting the carboxyl group in the thermosensitive polymer with the amino group in the amino-modified silica, and the growth factor is loaded in the pores of the silica; on the one hand, the biological macromolecule can undergo self-crosslinking, and on the other hand, the double bonds in the biological macromolecule undergo click chemical reaction with the thiol group in the thermosensitive polymer to crosslink; the biologically active peptide is prepared by modifying the side chain of the biological peptide with catechol, modifying the end group with methacrylic acid or acrylic acid, and the double bonds contained in the end methacrylic acid or acrylic acid undergo free radical crosslinking reaction with the double bonds of the biological macromolecule, and can also undergo click chemical reaction with the thiol group in the thermosensitive polymer to crosslink.
[0022] In general, the above technical solution conceived by the present invention has the following technical advantages compared with the prior art:
[0023] (1) The present invention uses biomacromolecules as the main body of the hydrogel gel structure, and self-crosslinks through the double bonds at the end to form a hydrogel. The hydrogel can make the adhesive form a structured main frame and have good mechanical properties; another part of the double bonds at the end of the biomacromolecule is cross-linked with the porous silica molecules grafted with the thermosensitive polymer, so that the porous silica microspheres grafted with the thermosensitive polymer are firmly combined with the biomacromolecule hydrogel, so that they are cross-linked in the hydrogel network. Since the thermosensitive polymer can play a good anti-swelling role, the anti-swelling effect of the adhesive as a whole can be improved, thereby avoiding the compression of the hydrogel swelling on blood vessels and soft tissues. The reason for selecting biomacromolecules with double bonds at the end is that the double bonds and thiol groups of the double bonds in the middle of the biomacromolecule cannot undergo cross-linking reaction.
[0024] (2) The present invention loads biological growth factors in the pores of silica. The growth factors loaded on silica can accelerate the healing of damaged tissues. At the same time, since the surface of silica is negatively charged, it can activate coagulation factors, activate the coagulation cascade reaction, and accelerate coagulation, thereby further improving the coagulation effect and accelerating wound healing.
[0025] (3) The methacrylic acid or acrylic acid at the end of the bioactive peptide undergoes a free radical cross-linking reaction with the double bonds at the end of the biomacromolecule, and can also undergo a click chemistry reaction with the porous silica grafted with a thermosensitive polymer to cross-link, so as to load the peptide into the hydrogel network and firmly bind it to the silica microspheres; the catechol structure of the side chain of the bioactive peptide plays a role in adhering to the skin, capturing red blood cells and platelets, and accelerating hemostasis.
[0026] (4) The biomacromolecules, bioactive peptides and drug-loaded porous silica grafted with thermosensitive polymers of the present invention are cross-linked with each other through chemical bonds to form a tight network structure, so that each functional group is firmly combined in the adhesive and is not easy to fall off, thereby achieving good technical effects of hemostasis, coagulation and anti-swelling. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The molecular structure of the bioactive peptide used for adhesion and hemostasis in the light-induced anti-swelling bioadhesive of the present invention;
[0028] Figure 2 is the anti-swelling ability of the light-induced anti-swelling bioadhesive in the present invention;
[0029] Figure 3 is the adhesion ability of the light-induced anti-swelling bioadhesive of the present invention to pig skin tissue;
[0030] Figure 4 The light-induced anti-swelling bioadhesive of the present invention has the ability to promote the proliferation of fibroblasts;
[0031] Figure 5 The light-induced anti-swelling bioadhesive of the present invention promotes blood coagulation activity;
[0032] Figure 6 The light-induced anti-swelling bioadhesive of the present invention has an adhesive and healing effect on mouse skin incisions;
[0033] Figure 7a The hemostatic effect of the light-induced anti-swelling bioadhesive of the present invention on mechanical injury of rat liver;
[0034] Figure 7bThe light-induced anti-swelling bioadhesive of the present invention promotes the healing effect of mechanical injury on rat liver. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0036] Example 1
[0037] Preparation of bioactive peptides: In this embodiment, the bioactive peptides were prepared by standard solid phase synthesis (SPPS) method, which has the biological activity of enhancing adhesion and rapid hemostasis, and specifically includes the following steps:
[0038] (1) Weigh 1.0 g of Rink Amide-MBHA resin into a peptide synthesis device, add analytical grade N,N-dimethylformamide (DMF) to swell the resin for 2 hours, and then use argon to pressurize and remove the solvent. Then use 10 ml of DMF solution containing 20% piperidine to deprotect the resin, react twice, each reaction time is 20 minutes, and wash the resin with DMF three times after the reaction. Then, take a small amount of resin and place it in an ethanol solution of ninhydrin and phenol, heat it to boiling, and observe that the color of the resin changes from white to purple, indicating that the resin is successfully deprotected and the amino acid coupling reaction can be carried out. Otherwise, the deprotection reaction needs to be continued.
[0039] (2) Weigh 0.8914 g of N-[(9H-fluorene-9-methoxy)carbonyl]-N'-[(2-propyleneoxy)carbonyl]-L-lysine (Fmoc-Lys(Alloc)-OH) and 1.0252 g of 1H-benzotriazol-1-yloxytripyrrolidinophosphonium hexafluorophosphate (PyBOP), dissolve them in 10 ml of DMF, and then transfer them to the peptide synthesis device containing the treated resin in step (1). Then add 690 μl of N,N-diisopropylethylamine (DIPEA) to the system and react at room temperature for 4 hours. Then wash the resin twice with 10 ml of DMF, add the materials again in the same proportion and react for another 4 hours to fully couple it to the resin. Finally, wash the resin three times with 10 ml of DMF, take a small amount of the resin and put it into an ethanol solution of ninhydrin and phenol, heat it to boiling, and observe that the resin does not change color, which means that the first amino acid is successfully coupled to the resin. Otherwise, the coupling reaction needs to be continued.
[0040] (3) Weigh 0.0758 g of tetrakis(triphenylphosphine)palladium and dissolve it in 10 ml of dichloromethane (DCM), then transfer the solution to the peptide synthesis device containing the treated resin in step (2), and then add 1943 μl of phenylsilane to the system to remove the lysine side chain protecting group. The reaction is repeated twice, each for 20 minutes. After the reaction is completed, the resin is washed with DMF amine three times. Subsequently, a small amount of resin is placed in an ethanol solution of ninhydrin and phenol, heated to boiling, and the color of the resin changes from white to purple, indicating that the lysine side chain is successfully deprotected and the subsequent amino acid coupling reaction can be carried out. Otherwise, the deprotection reaction needs to be continued.
[0041] (4) Take 170 μl of methacrylic acid and 1.0252 g of PyBOP, dissolve them in 10 ml of DMF, and then transfer them to the peptide synthesis device containing the treated resin in step (3), and then add 690 μl of DIPEA to the system and react at room temperature for 4 hours. Then wash the resin twice with 10 ml of DMF, add the materials again in the same proportion and react for another 4 hours to fully couple it to the resin. Finally, wash the resin three times with 10 ml of DMF, take a small amount of resin and put it in an ethanol solution of ninhydrin and phenol, heat it to boiling, and observe that the resin does not change color, which means that the amino acid and the lysine side chain are successfully coupled. Otherwise, it is necessary to continue the coupling reaction.
[0042] (5) Deprotect the first amino acid with 10 ml of DMF solution containing 20% piperidine, and react twice, each reaction time is 20 minutes. After the reaction, wash the resin with DMF three times. Then, take a small amount of resin and put it into an ethanol solution of ninhydrin and phenol, heat it to boiling, and observe that the color of the resin changes from white to purple, indicating that the first amino acid is successfully deprotected and the subsequent amino acid coupling reaction can be carried out. Otherwise, the deprotection reaction needs to be continued.
[0043] (6) Referring to step (2) and step (5), fluorenylmethoxycarbonyl-lysine (tert-butyloxycarbonyl) (Fmoc-Lys(Boc)-OH), Fmoc-Lys(Boc)-OH, fluorenylmethoxycarbonyl-phenylalanine (Fmoc-Phe-OH), fluorenylmethoxycarbonyl-L-glutamic acid 5-allyl ester (Fmoc-Glu(OAll)-OH), Fmoc-Phe-OH, Fmoc-Glu(OAll)-OH, Fmoc-Phe-OH, Fmoc-Glu(OAll)-OH, Fmoc-Phe-OH, Fmoc-Glu(OAll)-OH, Fmoc-Phe-OH, Fmoc-Glu(OAl1)-OH, Fmoc-Lys(Boc)-OH, Fmoc-Lys(Boc)-OH, and methacrylic acid are condensed in sequence.
[0044] (7) Weigh 0.0462 g of tetrakis(triphenylphosphine)palladium and dissolve it in 10 ml of DCM. Then transfer the solution to the peptide synthesis apparatus containing the treated resin in step (6). Then add 1455 μl of phenylsilane to the system to remove the glutamic acid side chain protecting group. The reaction is repeated twice, each for 30 minutes. After the reaction, the resin is washed three times with DMF.
[0045] (8) Weigh 0.9307 g dopamine and 2.5520 g PyBOP, dissolve them in 10 ml DMF, and then transfer them to the peptide synthesis device containing the treated resin in step (7). Then add 820 μl DIPEA to the system and react at room temperature for 4 hours. Then wash the resin twice with 10 ml DMF, add the materials again in the same ratio and react for another 4 hours to fully couple to the resin. Finally, wash the resin three times with 10 ml DMF.
[0046] (9) The resin was washed three times with 10 ml of DCM, methanol, and DCM, respectively, and then dried using a vacuum oil pump for 1 hour.
[0047] (10) Add 9.5 ml of trifluoroacetic acid (TFA), 0.25 ml of triisopropylsilane (TIS), and 0.25 ml of deionized water to the peptide reaction device and react at room temperature for 3 hours to cleave the peptide from the resin. Slowly add the cleavage solution dropwise into ice ether, and a white precipitate will appear. Then centrifuge at 3000 rpm for 10 minutes to separate the crude product, discard the supernatant, dissolve the precipitate with an appropriate amount of methanol, purify the product through a medium pressure purification chromatography system, and finally freeze-dry to collect the white powder, thus obtaining an adhesion and hemostatic bioactive peptide with the sequence of Methacrylic Acid-Lysine-Lysine-Glutamic Acid (Dopamine)-Phe-Alanine-Glutamic Acid (Dopamine)-Phe-Alanine-Glutamic Acid (Dopamine)-Phe-Alanine-Glutamic Acid (Dopamine)-Phe-Alanine-Lysine-Lysine-Methacrylic Acid-Lys-Lys-Glu (Dopamine)-Phe-Glu (Dopamine)-Phe-Glu (Dopamine)-Phe-Lys-Lys-Lys (Methacrylic Acid). The molecular structure of the prepared bioactive peptide is as follows: Figure 1 shown.
[0048] Example 2
[0049] Preparation of drug-loaded porous silica grafted with thermosensitive polymers:
[0050] (1) Preparation of thiol- and carboxyl-modified thermosensitive polymers:
[0051] 1 g of N-isopropylacrylamide (NIPAM) monomer, 0.0123 g of dithiobenzoic acid 4-cyanovaleric acid, and 0.0036 g of azobisisobutyronitrile (AIBN) were added to an ampere tube, and then 1 ml of LDMF was added to dissolve, nitrogen was introduced to deoxygenate and the tube was sealed, and the ampere tube was stirred in a 60°C water bath for 24 hours, and then a small amount of DCM was added, and then it was slowly added to a large amount of ether for precipitation, and then vacuum dried at 30°C to obtain orange powdered carboxyl-modified poly N-isopropylacrylamide (PNIPAM-COOH).
[0052] In a clean single-necked flask, 0.37 g of the prepared PNIPAM-COOH was added, followed by 87 μL of ethanolamine and 9.5 mL of tetrahydrofuran (THF) solvent, and then nitrogen was introduced to deoxygenate and the flask was sealed. The flask was reacted at room temperature for 24 h, and then precipitated in ice ether, and then vacuum dried to obtain thiol- and carboxyl-modified poly (N-isopropylacrylamide) (HS-PNIPAM-COOH).
[0053] (2) Preparation of porous silica loaded with growth factors grafted with thermosensitive polymers:
[0054] Amino modification of silicon dioxide: weigh 150 mg of surfactant (CTAB) and 50 ml of deionized water in a measuring cylinder and add them to the reaction bottle, and place in a water bath at 30°C for 15 minutes. Then add 2.5 ml of methanol, 10 ml of ethyl acetate and 1.5 ml of ammonia water to the reaction bottle in sequence. After reacting in the reaction bottle for 20 minutes, add 220 ul of tetraethyl orthosilicate (TEOS) and react for 3 hours. After 3 hours, add 30 ul of 13-aminopropyltriethoxysilane (APTES) and react for 3 hours. After 3 hours, centrifuge the mixed solution in the reaction bottle at a centrifuge speed of 8000 r / r / min for 8 minutes, then pour out the supernatant, add appropriate hydrochloric acid ethanol solution (ethanol / HCL=10 / 1) to each centrifuge tube for ultrasonic dispersion, so that it is evenly distributed in the solution, and then centrifuge at a speed of 8000 r / r / min. The above acid washing operation is repeated three times. Then wash with water 3 times. Amino-modified expanded-pore silica nanoparticles (SiO2-NH2) can be obtained.
[0055] Amino-modified silica is grafted with thermosensitive polymers modified with thiol and carboxyl groups: 96 mg of 1-ethyl-(3-dimethylaminopropyl) carbodiimide (EDC) and 48 mg of N-hydroxysuccinimide (NHS) are weighed and added to an appropriate reaction bottle, and then 400 ul of deionized water is added to dissolve. 2 ml of the prepared 5 mg / ml HS-PNIPAM-COOH solution is added to the reaction bottle, and 5 ml of 1 mg / ml amino-modified expanded pore silica (SiO2-NH2) nanoparticles are added to the reaction bottle. After 24 hours, the speed is 7500 r / min, 8 min centrifugation, and washed three times with water. The carboxyl group in HS-PNIPAM-COOH undergoes an amidation reaction with the amino group in the amino-modified silica, and the porous silica grafted with the thermosensitive polymer, i.e., HS-PNIPAM-CONH-SiO2, is obtained.
[0056] Loading biological growth factors: Take 5 mg of 10 mg / ml HS-PNIPAM-CONH-SiO2 solution and centrifuge at a speed of 7500 r / r / min for 5 minutes, remove the supernatant, take 0.2 ml (5 mg) of 25 mg / ml growth factor solution and add it to a centrifuge tube, put it in a shaker (37°C, 120 rpm) for incubation for 24 hours after ultrasonic dispersion, then put it in a vacuum drying oven (37°C) for negative pressure packing, add 0.5 ml of ice sterile water, centrifuge it after cooling (8000 r / r / min, 6 minutes). Add ice sterile water again and repeat the above operation. The porous silica loaded with growth factors grafted with thermosensitive polymers is obtained.
[0057] Example 3
[0058] The preparation of the light-induced anti-swelling bioadhesive comprises the following sub-steps:
[0059] (1) Weigh 100 mg of methacrylamide gelatin (purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., catalog number: G477883), 20 mg of the bioactive peptide prepared in Example 1, 100 mg of porous silica loaded with alkaline fibroblast growth factor grafted with thiol-modified poly (N-isopropylacrylamide), and 2 mg of phenyl-2,4,6-trimethylbenzoyl lithium phosphite (LAP) as an initiator, dissolve them in 1 ml of physiological saline, mix them evenly, and degas to obtain a prepolymer solution.
[0060] (2) The bioadhesive prepolymer solution is dripped onto the application site, and then the prepolymer solution is photocured by blue light irradiation to form the bioadhesive.
[0061] Results and Characterization:
[0062] (1) Anti-swelling performance test of adhesive
[0063] The anti-swelling property of the light-induced anti-swelling bioadhesive prepared in Example 3 was tested to evaluate the compression of the bioadhesive provided by the present invention on soft tissues.
[0064] The initial mass of the light-induced anti-swelling bioadhesive prepared in Example 3 was recorded. Subsequently, it was placed in physiological saline at 4°C and 37°C for 1, 3, and 5 days, respectively, to allow it to absorb water to a saturated equilibrium state. After it was taken out, the surface liquid was wiped off with filter paper, and the final mass was recorded. The swelling rate was calculated as follows: swelling rate = (final mass - initial mass) / initial mass × 100%. Figure 2 It can be seen that based on the heat shrinkage of the thermosensitive polymer at 37°C in the physiological environment, the light-induced anti-swelling bioadhesive has good anti-swelling properties, avoiding the compressive damage of the adhesive to the soft tissue.
[0065] (2) Adhesion test of adhesive to pig skin tissue
[0066] The adhesion ability of the light-induced anti-swelling bioadhesive prepared in Example 3 to pig skin tissue was tested to evaluate the adhesion performance of the bioadhesive provided by the present invention to skin.
[0067] Specifically, the prepolymerized liquid of the bioadhesive obtained in step 2 of Example 3 was dripped onto the pig skin, and then irradiated with blue light to initiate photocuring of the prepolymerized liquid to form the bioadhesive. Finally, the pig skin was stretched, bent, twisted, soaked, and rinsed to observe the adhesion between the bioadhesive and the skin tissue. Figure 3 The results showed that the bioadhesive remained tightly adhered to the pig skin tissue after being stretched, bent, twisted, soaked, and rinsed, indicating that the light-induced anti-swelling bioadhesive had a strong adhesion ability to pig skin tissue.
[0068] (3) Test of the ability of adhesives to promote proliferation of fibroblasts
[0069] The ability of the light-induced anti-swelling bioadhesive prepared in Example 3 to promote the proliferation of fibroblasts was tested to evaluate the promoting effect of the bioadhesive provided by the present invention on tissue healing at the cellular level.
[0070] The light-induced anti-swelling bioadhesive prepared in Example 3 was co-incubated with mouse embryonic fibroblasts, and cell proliferation was evaluated by live-dead staining after 5 days. Figure 4 The results showed that light-induced anti-swelling bioadhesive could promote fibroblast proliferation, thereby promoting tissue healing.
[0071] (4) Adhesive promoting blood coagulation activity test
[0072] The ability of the light-induced anti-swelling bioadhesive prepared in Example 3 to accelerate blood coagulation was tested to evaluate the rapid hemostatic function of the bioadhesive provided by the present invention.
[0073] After the light-induced anti-swelling bioadhesive prepared in Example 3 was co-incubated with blood, the blood coagulation time was recorded. Figure 5 The results show that the light-induced anti-swelling bioadhesive can accelerate blood coagulation, thereby achieving rapid hemostasis. The experimental group used the prepared light-induced anti-swelling bioadhesive, and the control group did not use the adhesive.
[0074] (5) Test on the adhesion and healing effect of adhesive on mouse skin incision
[0075] The light-induced anti-swelling bioadhesive prepared in Example 3 was tested for its bonding and healing effects on mouse skin incisions, thereby proving that the bioadhesive provided by the present invention can achieve tissue bonding, effectively replace surgical sutures, quickly close wounds and accelerate healing.
[0076] The prepolymerized bioadhesive obtained in step 2 of Example 3 was dripped onto the mouse skin incision, and then the incision was closed and irradiated with blue light to initiate photocuring of the prepolymerized bioadhesive to achieve bonding. The healing conditions of the bioadhesive group and the surgical suture group were evaluated after 10 days. Figure 6 The results showed that the healing speed of the light-induced anti-swelling bioadhesive group was faster than that of the control group and the surgical suture group, indicating that the bioadhesive can effectively replace surgical sutures, quickly close wounds and accelerate healing. The experimental group used the prepared light-induced anti-swelling bioadhesive, the control group did not intervene after the incision was formed, and the suture group used needle and thread to suture the wound.
[0077] (6) Test on the hemostatic and healing effects of adhesives on mechanical liver injury in rats
[0078] The light-induced anti-swelling bioadhesive prepared in Example 3 was tested for its hemostatic and healing effects on mechanical liver injury in rats, thereby proving that the bioadhesive provided by the present invention can achieve effective blocking and accelerated healing of bleeding tissue.
[0079] The prepolymerized bioadhesive obtained in step 2 of Example 3 was dripped onto the mechanical injury wound of rat liver, and then irradiated with blue light to initiate photocuring of the prepolymerized bioadhesive to seal the bleeding tissue. The healing of the injury was observed by pathological tissue sections after 5 days. Figure 7a The results showed that the light-induced anti-swelling bioadhesive could accelerate hemostasis of mechanically injured liver tissue; Figure 7bThe results showed that the light-induced anti-swelling bioadhesive could promote the repair of mechanical damage to liver tissue. The experimental group used the prepared light-induced anti-swelling bioadhesive, while the control group did not use the adhesive.
[0080] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A light-induced anti-swelling bioadhesive, characterized in that: The invention comprises biological macromolecules, bioactive peptides and porous silica grafted with thermosensitive polymers. The biological macromolecules and the porous silica grafted with thermosensitive polymers form a hydrogel network structure through crosslinking reaction, and the bioactive peptides are connected with the biological macromolecules through free radical crosslinking reaction.
2. The light-induced anti-swelling bioadhesive according to claim 1, characterized in that The chain ends of the biomacromolecules contain double bonds.
3. The light-induced anti-swelling bioadhesive according to claim 2, characterized in that The biomacromolecule is one or more of methacrylamide gelatin, methacrylamide silk protein, methacrylamide hyaluronic acid, methacrylamide chondroitin sulfate, methacrylamide sodium alginate, methacrylamide chitosan, methacrylamide dextran, methacrylamide heparin, polyether diacrylate, polyethylene glycol diacrylate, four-arm polyethylene glycol acrylate, and methacrylamide polyvinyl alcohol.
4. The light-induced anti-swelling bioadhesive according to claim 1, characterized in that The porous silica grafted with the thermosensitive polymer is obtained by connecting the carboxyl group in the thermosensitive polymer with the amino group in the amino-modified silica through reaction grafting. Preferably, the thermosensitive polymer is poly-N-isopropylacrylamide modified with thiol and carboxyl groups.
5. The light-induced anti-swelling bioadhesive according to claim 1, characterized in that The pores of the porous silica grafted with the thermosensitive polymer are loaded with biological growth factors, and preferably the biological growth factors are one or more of epidermal growth factor, fibroblast growth factor, nerve growth factor, platelet-derived growth factor and transforming growth factor.
6. The light-induced anti-swelling bioadhesive according to claim 1, characterized in that The bioactive peptide is prepared by modifying the side chain of the biopeptide with catechol, and the terminal group of the biopeptide is modified with methacrylic acid or acrylic acid.
7. The method for preparing the light-induced anti-swelling bioadhesive according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) dissolving biomacromolecules, bioactive peptides, porous silica grafted with thermosensitive polymers, and initiators in physiological saline, uniformly mixing, and degassing to obtain a prepolymer solution; (2) The prepolymer solution is then irradiated with ultraviolet light or blue light to initiate photocuring of the prepolymer solution to form a bioadhesive.
8. The method for preparing the light-induced anti-swelling bioadhesive according to claim 7, characterized in that: The amount of biomacromolecules in the prepolymer solution is 5wt%-20wt%, the amount of bioactive peptides in the prepolymer solution is 1wt%-5wt%, the amount of drug-loaded porous silica grafted with thermosensitive polymer in the prepolymer solution is 5wt%-20wt%, and the amount of initiator in the prepolymer solution is 0.1wt%-5wt%.
9. The method for preparing the light-induced anti-swelling bioadhesive according to claim 7, characterized in that: The initiator is selected from one or more of 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, phenyl-2,4,6-trimethylbenzoyl lithium phosphite, and Eosin Y. When the prepolymer liquid used is Eosin Y, a co-initiator is required, and the co-initiator is preferably one or both of triethanolamine and pentamethyldiethylenetriamine.
10. Use of the light-induced anti-swelling bioadhesive according to any one of claims 1 to 6 in the preparation of a bioadhesive for promoting adhesion and repair of biological tissues or for occluding and stopping bleeding of blood vessels.
